Understanding the nursing team in the assistance to the schizophrenic patient - Danielle Uehara de Lima; Ana Paula Rigon Francischetti Garcia; Vanessa Pellegrino Toledo (Rev Rene)
The goal is to comprehend the perception of the nursery team during the schizophrenic patient assistance. It’s an exploratory and descriptive study, performed in the psychiatric unit of a university hospital. Data collection was realized with fifteen nursing professionals, through semi-structured interviews. Data analysis revealed three categories: the look that highlights the common sense to guide the provided care; the care that recognizes the importance of the nurse and patient relationship, apart from their theoretical assumptions; to feel, where fear and frustration typify the assistance; It was evident that professionals fail to organize their perceptions about the relationship with the patient, due to lack of support and theoretical method to establish it, merely an interpretation based on common sense, which is a stage for the formation of nursing science. Transpose the limit requires preparation for professional practice, and the issues raised encourage further studies to consolidate care.